The role of individual differences in occupational stress and well being - Perrewe, Pamela L.; Ganster, Daniel C. (Emerald, 2011)
This annual research series is devoted to the examination of occupational stress, health and well being, with particular emphasis on the multi-disciplinary nature of occupational stress. Titles pull together the various streams of research from a variety of disciplines to better capture the significant bodies of work in occupational stress and well being. Volume 9 specifically examines the role of individual difference in occupational stress, health and well being. Individual differences include emotion, personality and even differences in cognition. Seven chapters by authors from three countries and six states, from professions including psychology, sociology and management, analyse topics such as: emotion regulation; narcissism; cognitive adaptation; resiliency; individual differences as they relate to high-risk professions; and resources as they relate to entitled employees. This volume provides a thorough and critical assessment of knowledge, and gaps in knowledge, in this engaging area of interest in the field of occupational stress. It is highly recommended reading for academic and government researchers in psychology, business, health and well being, education and sociology.
Keywords: Job stress.; Psychology, Industrial.; elektronické knihy; electronic books